Injury prevention programmes: What helps? - Bizzini, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Most football injuries are caused by foul play: Fair Play and stricter application of the Laws of the Game are crucial in the prevention of contact injuries (few publications at today). However, non-contact injuries can be reduced with multi-modal programmes, as originally published by Ekstrand in the 80`s. Further, two exercise-based prevention programmes, the PEP (Gilchrist 2008) and moreover "The 11+" (Soligard et al 2008), were able to significantly reduce the incidence of lower extremity injuries in female college players. Similar results in term of injury reduction (ca. 50%) have been recently found in a large RCT in male US soccer teams adopting the FIFA 11+ as a standard warm up (Silvers et al 2015). Research has further reinforced the importance of neuromuscular control in sports injury prevention (Herman et al 2012). Specific eccentric exercises have shown to significantly reduce the incidence of new and recurrent hamstring injuries in male players (Petersen et al 2011). Countrywide prevention campaigns in amateur football (Junge et al 2011) showed both an overall reduction of injuries and of health-care related costs. Despite these findings, the dissemination and implementation of injury prevention programmes in the real world of sport, and moreover at community level, remains a major challenge.